Equilibrium point-based control of muscle-driven anthropomorphic legs reveals modularity of human motor control during pedalling. (3rd March 2020) - Watanabe, Eichi; Hirai, Hiroaki; Krebs, Hermano Igo
ABSTRACT: This study aims at shedding new light on the human motor control during forward and backward pedalling motions from a viewpoint of the mechanical impedance, determined by the coordinated activations of multiple pairs of agonist-antagonist muscles, called equilibrium point (EP)-based synergy. First, human movements and electromyograms as muscle activations during forward and backward pedalling motions were measured, and using our working model proposed earlier, they were analysed to obtain EP-based synergies, i.e. a set of synergy vectors and the corresponding time-courses of synergy activation coefficients associated with a virtual trajectory, for each pedalling direction. We showed the similarity in the EP-based synergies between forward and backward motions. We performed a robot experiment, where we used the EP-based synergies for the forward pedalling with their time-reversed synergy activation coefficients and a phase-shift in a coefficient for a specific synergy vector to actuate a robot of muscle-driven anthropomorphic legs for achieving a backward pedalling. Comparisons between the backward motion in the robot and that in human confirmed that they were mostly the same. Our results support our working model that the human motor control shares the common EP-based synergy and the associated mechanical impedance for controlling the forward and backward pedalling motions. GRAPHICAL ABSTRACT: